Iridium Complexes with BIAN-Type Ligands: Synthesis, Structure and Redox Chemistry; International Journal of Molecular Sciences; Vol. 24, iss. 13 - Romashev N. F. Nikolai; Bakaev I. V. Ivan; Komlyagina V. I. Veronika; Abramov P. A. Pavel Aleksandrovich; Mirzaeva I. V. Irina (2023, 2023)
Title screen